2018
DOI: 10.1016/j.jretconser.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Advertisements on Facebook: Identifying the persuasive elements in the development of positive attitudes in consumers

Abstract: The main objective of this study is to develop the scale items of consumers' attitudes toward Facebook advertisements and to theorize consumers' attitudinal behaviour. To undertake this study, a research assistant was appointed, who is also an active member of Facebook, to introduce a message about the product Samsung Tab S, and to pass it to other members of their network. From this experiment, different members of their network participated in generating, passing, and receiving messages to develop a prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 60 publications
(87 reference statements)
0
59
0
6
Order By: Relevance
“…In the Internet era, consumers increasingly look for information about products and services online to enhance their purchase decision process (Alalwan 2018;Dwivedi et al, 2015;Lee et al, 2008;Shareef et al, 2017;Shiau et al, 2018). Consumers who used advertising communications and professional advice a few years ago, now more often use recommendations provided by other online consumers (Lee et al, 2008;Misirlis and Vlachopoulou, 2018;Purnawirawan et al, 2015;Shareef et al, 2018). Electronic word of mouth (eWOM) is defined as "the dynamic and on-going information exchange process between potential, actual, or former customers regarding a product, service, brand or company, which is available to a multitude of people and institutions via the Internet" (Ismagilova et al, 2017, p.18).…”
Section: Introductionmentioning
confidence: 99%
“…In the Internet era, consumers increasingly look for information about products and services online to enhance their purchase decision process (Alalwan 2018;Dwivedi et al, 2015;Lee et al, 2008;Shareef et al, 2017;Shiau et al, 2018). Consumers who used advertising communications and professional advice a few years ago, now more often use recommendations provided by other online consumers (Lee et al, 2008;Misirlis and Vlachopoulou, 2018;Purnawirawan et al, 2015;Shareef et al, 2018). Electronic word of mouth (eWOM) is defined as "the dynamic and on-going information exchange process between potential, actual, or former customers regarding a product, service, brand or company, which is available to a multitude of people and institutions via the Internet" (Ismagilova et al, 2017, p.18).…”
Section: Introductionmentioning
confidence: 99%
“…SCRM issues have been the focus of a number of recent studies (i.e. [5,15,26,30,41]. Some of these studies (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…eWOM is defined as "the dynamic and ongoing information exchange process between potential, actual, or former consumers regarding a product, service, brand or company, which is available to a multitude of people and institutions via the Internet" (Ismagilova et al, 2017, p.18). Studies have found positive relationships between eWOM and information adoption (Chang & Wu, 2014;Wang et al, 2015), change in attitude (Hsu et al, 2013;Huang & Korfiatis, 2015;Martin & Lueg, 2013;Pan & Chiou, 2011;Shareef et al, 2018), purchase intention (Bi et al, 2017;Chen et al, 2016;Hernandez & Handan, 2014;Pappas, 2016;Pereira et al, 2016;Plotkina & Munzel, 2016;Pookulangara & Koesler, 2011;Sweeney et al, 2014;Weisstein et al, 2017) and sales of products/services (Blal & Sturman, 2014;Cadario, 2014;Eslami & Ghasemaghaei, 2018;. However, information overload from vast quantities of eWOM can cause confusion and result in a negative effect on purchase intention (Furner & Zinko, 2017;Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%